The AI-Powered Diagnosis: Can Artificial Intelligence Truly Improve Your Diagnostic Accuracy? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The question of whether Artificial Intelligence AI can improve diagnostic accuracy is one of the most critical inquiries in modern digital health. Diagnostic...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care